Globularia alypum Extracts Attenuate Hyperglycemia and Protect against Various Organ Toxicities in Alloxan-Induced Experimental Diabetic Rats. (30th August 2022) - Tiss, Mohamed; Hamden, Khaled
Abstract : In this study, we attempted for the first time to determine the phytochemical compositions and biopharmaceutical properties of Globularia alypum methanol extract (GAME) and Globularia alypum water extract (GAWE). High-performance liquid chromatography with diode array detection (HPLC-DAD) analysis was performed to establish the chemical profile of the investigated extracts. Chemical composition analysis was taken in the presence of various bioactive compounds such as quercetin 7-O-glucoside and apigenin 7-O-glucoside in GAME. In GAWE, various abundant compounds were found in the extract such as quercetin 7-O-glucoside, apigenin, quercetin, apigenin 7-O-glucoside, and cinnamic acid. This study showed that the administration of GAWE and GAME to type 1 diabetic rats decreased fasting blood glucose, protected pancreas β -cells from death and injury, increased liver glycogen rate, and ameliorated oral glucose tolerance test. Moreover, GA reduced weight loss, and diabetes decreased basic physical activity. In addition, the administration of GA extracts in diabetic rats protected from diabetes-induced liver, kidney, testes, heart, and bone toxicities. Conclusion. GAWE has possible value for antidiabetic oral medication.